Digestive stability and transport ability changes of β-lactoglobulin–catechin complexes by M cell model in vitro - Dai, Yan; Yang, Ruoting; Yan, Yuting; Wu, Yong; Meng, Xuanyi; Yang, Anshu; Wu, Zhihua; Shi, Linbo; Li, Xin; Chen, Hongbing (Frontiers in Nutrition, 2022)
The current research on interaction between catechin and protein has focused on non-covalent crosslinking, however, the mechanism of free radical-induced crosslinking between catechin and β-lactoglobulin (BLG) is not known. In this study, BLG bound to four catechins [epicatechin (EC), epigallocatechin (EGC), epicatechin gallate (ECG), and epigallocatechin gallate (EGCG)]. The structure change of complex was investigated by circular dichroism spectroscopy, ultraviolet-visible (UV-vis) spectroscopy and Acid and 8-Anilino-1-naphthalenesulfonic acid (ANS) fluorescence spectroscopy. M cell model was constructed to evaluate the transintestinal epithelial transport capacity of complex digestive products. The results showed that catechins were covalently bound to BLG by C-S and C-N bonds and their binding content was EGCG>EGC>ECG>EC. Moreover, catechins could change the secondary structure of BLG, with the decrease of α-helix and reduction of the irregular coilings, which leads to the loose spatial structure of the protein. Moreover, the catechin could enhance further the digestibility of BLG. Transport capacity of digestive products of M cell model was about twice of that of the Caco-2 cell model, indicating that M cell model had better antigen transport capacity. The difference between groups indicated that the transport efficiency of digestive products was decreased with the presence of catechin, in which BLG-EGCG and BLG-EGC groups were transported more strong than those of BLG-EC and BLG-ECG groups. The transport efficiency of BLG-catechin complexes were lower than that of BLG, indicating that catechin had the protective and repair roles on intestinal barrier permeability.